The fishing profession’s role in constructing a pantribal identity of the Imraguen community in Mauritania - Bahdah, Yacoub (Journal of Humanities & Social Sciences, 2019)
This artice discusses an issue of a great paramount in soccio-anthrpological studies in general, and in tribal societies in particular. The article studies the “Imraguen” community which was formed on the basis of a common profession discarding the traditional tribal frames in a society where the tribe had a strong status and a crucial role in individuals’ relations. The article aims at uncovering the considerations of a shared profession, fishing, in the formation of this community as well as how families and clans from different tribes, who came together over centuries, could form a homogeneous community living on fishing unlike the broader Bidhan community’s nomadic desert lifestyle. Data was collected through observations, interviews and a historical approach. The information gathered through the observations helped interview some Imraguen individuals to probe for further information. The historical method helped understand the community’s genealogical, cultural and functional/vocational characteristics for a better understanding of the community’s current status and how it maintained its fishing profession and inter-community relations over the years.